Improving global public goods supply through conditional transfers: The international adaptation transfer riddle - Pittel Karen; Dirk Rübbelke (Center for Economic Studies and ifo Institute (CESifo), 2013)
In order to overcome the underprovision of global public goods various different policy approaches have been proposed. In the climate policy arena, international transfers are frequently seen as an effective means to raise the provision of the global public good 'climate change mitigation'. This paper focuses on a specific type of international transfer that aims at raising mitigation while also reducing the damages from climate change: conditional adaptation support. Especially since the COP in Copenhagen 2009, preparations are on-going to significantly expand international transfers that help developing countries to adapt to climate change. While there are extensive discussions in the policy arena about the required amount of adaptation funding and the best ways to raise, manage and disburse these funds, hardly any attention is paid to the international allocative effects of these transfers. The answer to the question of 'why' international adaptation transfers are paid at all, is often relegated to fairness considerations only. As adaptation benefits are largely local and adaptation transfers reduce the recipients' incentives to contribute to climate change mitigation, one would, however, expect at least unease in donor countries about plans to significantly expand international adaptation support. In this study, we compare two alternative conditional transfer schemes: one plainly subsidizes mitigation efforts, while the other provides adaptation support which is conditional on other agents' mitigation contributions. Disregarding distributional and fairness aspects the paper evaluates and compares the allocative effects of either policy scheme. It is shown that while both policy schemes can be beneficial for developing as well as industrialized countries, this outcome relies strongly on the productivity of mitigation and adaptation technologies.
Keywords: H41; H87; Q54; 330; voluntary public good provision; conditional transfers; international climate policy; adaptation; mitigation; Öffentliches Gut; Internationaler Transfer; Klimaschutz; Entwicklungshilfekonditionen; Welt